Cost analysis of a watch‐and‐wait approach in patients with a complete clinical response to chemoradiotherapy for rectal cancer. Issue 11 (19th July 2022) - Cooper, Edward A.; Hodder, Rupert J.; Finlayson, Andrew; Filgate, Rhys; Coveney, Andrew; Balasuriya, Hasitha Dinesh; Warner, Michael W.
Abstract: Background: There is increasing interest in the watch‐and‐wait approach for patients with rectal cancer who have had a complete clinical response following neoadjuvant long course chemoradiotherapy. This study is a cost analysis of expenditure on patients in the watch‐and‐wait program versus patients who underwent standard rectal resection followed by routine surveillance. Methods: Data were prospectively collated and retrospectively analysed in all patients who presented with rectal cancer from January 2016 to January 2018 at Sir Charles Gairdner Hospital, Perth, Western Australia. Software developed by the North Metropolitan Health Service was used to capture comprehensive data to calculate the in‐hospital expenditure for an individual patient throughout their treatment journey. Results: For a patient enrolled in the watch‐and‐wait pathway, the total cost of surveillance over a 5‐year period was $45 246. This was compared with the cost of an ultra‐low anterior resection/loop ileostomy/closure of loop and routine postoperative surveillance which came to a total of $87 473. While a patient who had an abdominoperineal resection followed by routine 5‐year surveillance had an expenditure of $82 290. Conclusion: There is growing evidence that the watch‐and‐wait strategy is a valid management option. In the cost‐conscious environment of the current health care system, the watch‐and‐wait pathway is a cost‐effective and economically advantage treatment. Abstract : Rectal preservation following a complete clinical response of a rectal tumour is gaining increasing interest worldwide but is not yet standard of care in Australia. This paper aims to provide an interesting insight into an Australian experience of a watch‐and‐wait regimen and its associated costs when compared with upfront TME resection and routine surveillance.